The disparities of dental anxiety in adult dental patients: a sociodemographic and dental visit experience analysis - Dewi, Alifia Rahma; Mayasari, Yufitri (Faculty of Dentistry Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Patient anxiety can impede dental treatment adherence. Several factors influence patient anxiety, including sociodemographic characteristics and prior dental visit experiences. This study aims to analyze the disparities of dental anxiety in adult dental patients from sociodemographic and dental visit experience analysis point of view. Methods: Type of research was cross-sectional study. The population was all dental patients during May 30th and June 16th, 2023 at the Cipondoh Public Health Center in Tangerang City. Sixty-one patients were purposely sampled from the dental clinic. Data were collected via a self-administered questionnaire containing five questions regarding sociodemographic factors and dental visit experiences. Each question offered respondents five response options, represented by scores. Anxiety was measured using the Modified Dental Anxiety Scale (MDAS), and statistical analysis was performed using SPSS version 26 with Mann-Whitney, ANOVA, Kruskal Wallis tests. Results: Among the 61 participants, 33.1% reported experiencing dental anxiety, with an average MDAS score of 8.92. Comparative analysis revealed significant differences in anxiety scores based on age (p<0.05), gender (p<0.05), education level (p<0.05), and dental visit experience (p<0.05). Conclusion: There are significant anxiety differences in adult patients based on sociodemographic factors, including gender, age, educational level, and dental experience factors. Keyword : dental anxiety, socioeconomic factors, dental visit, adult